A New Technique for the Assessment of Cerebral Vasodilatory Capacity as Part of Catheter-Based Cerebral Angiography - Qureshi, Adnan, I; Gurkas, Erdem; Aytac, Emrah; Asif, Ahmer; Waqas, Muhammad A.; Wallery, Shawn S. (Lippincott Williams & Wilkins, 2019)
[Abstract Not Available]
American-Heart-Association/American-Stroke-Association International Stroke Conference / State-of-the-Science Stroke Nursing Symposium -- FEB 06-08, 2019 -- Honolulu, HI